Critical Thinking in Indonesian Language Learning - Alwandi Yanta Krisna; Urip Sulistiyo; Rustam (LPPM Undiksha, 2024)
Teachers need help in educational reform in planning, learning processes, and evaluation due to errors in identifying technical problems, especially in Indonesian language learning. This certainly has an impact on students' poor critical thinking skills. This research aims to analyze critical thinking in Indonesian language learning. This research was conducted using a mixed method approach. This type of research uses a Systematic Literature Review (SLR). The method used to collect data is documentation. The data sources used are the Garuda Portal database and Google Scholar, done with the help of Publish or Parish. 8. The data collection technique uses a Prism Diagram. The techniques used to analyze data are qualitative descriptive analysis and quantitative analysis. The results of this research are the publication of articles on critical thinking in learning Indonesian from several of the most productive years in 2022 and 2023, with 17 articles and 34 articles published from the Garuda portal and Google Scholar databases. Integrating critical and creative thinking skills in Indonesian language learning in SD/MI can help improve students' ability to understand, produce, and use language better. In an implementation, starting with learning planning, learning processes, and learning evaluation, there is an implementation in applying critical thinking in Indonesian language learning.